1996
DOI: 10.1034/j.1600-0501.1996.070302.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of abutment surface roughness on plaque accumulation and peri‐implant mucositis

Abstract: Bacterial adhesion to intra-oral, hard surfaces is firmly influenced by the surface roughness to these structures. Previous studies showed a remarkable higher subgingival bacterial load on rough surfaces when compared to smooth sites. More recently, the additional effect of a further smoothening of intra-oral hard surfaces on clinical and microbiological parameters was examined in a short-term experiment. The results indicated that a reduction in surface roughness below R(a) = 0.2 microns, the so-called "thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
428
6
25

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(483 citation statements)
references
References 0 publications
24
428
6
25
Order By: Relevance
“…Shintani (14) reported that plaque adhesion increases on rougher surfaces. In contrast, Bollen et al reported that Ra values less than 0.2 µm do not affect bacterial adhesion (28), and a study by Nascimento et al showed that bacterial adhesion to titanium and zirconium was insensitive to Ra (29). However, Dorkhan et al reported high bacterial adhesion on rough surfaces coated with saliva (30) and found that adhesion to composite resin is not influenced by surface characteristics.…”
Section: Discussionmentioning
confidence: 82%
“…Shintani (14) reported that plaque adhesion increases on rougher surfaces. In contrast, Bollen et al reported that Ra values less than 0.2 µm do not affect bacterial adhesion (28), and a study by Nascimento et al showed that bacterial adhesion to titanium and zirconium was insensitive to Ra (29). However, Dorkhan et al reported high bacterial adhesion on rough surfaces coated with saliva (30) and found that adhesion to composite resin is not influenced by surface characteristics.…”
Section: Discussionmentioning
confidence: 82%
“…Generally, rough surfaces promote bacterial adhesion whereas smooth surfaces minimize it [13][14][15] . According to Bollen et al 16) , surface roughness below Ra=0.2 m had no further quantitative and qualitative effects on bacterial adhesion. Moreover, variations around this value had only a negligible impact on bacterial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies confirm that a roughness of Sa= 0.2 μm can be accepted as a threshold; significantly exceeding this promotes the risk of mechanical plaque retention. 13 However, 4 roughness should not be critically below this threshold to facilitate soft-tissue adherence and avoid loss of attachment.…”
Section: Introductionmentioning
confidence: 99%